Memória e acervo no teatro: um estudo de caso do acervo audiovisual do CPMT do Centro Cultural Galpão Cine Horto - Carvalho, Alessandro Brito (2015)
As an audiovisual technician from the Theater Course at the Federal University of Uberlândia, I searched for subsidies to make an audiovisual archive of the above- mentioned course. For this purpose, I have done this research in the form of a case study about the founding and maintenance of the audiovisual archives of the CPMT - Centro de Pesquisa e Memória do Teatro (Center of Theater Research and Memory), located at the Centro Cultural Galpão Cine Horto (Belo Horizonte-MG), an institution affiliated to Grupo Galpão de Teatro (Group Galpão of Theater). To this end I reflect on the concepts of memory, information and audiovisual, associating these concepts to the field of theater. Two field surveys were conducted consisting of interviews with students, teachers and managers from the Centro Cultural. The research presents the following structure: in the first chapter, I reflect on the concepts of memory, information, documentation, associating the discussion to the fleeting character of theater art. For this, I base myself on the studies of Jacques Le Goff on the concept of document/monument and Pierre Nora on the realms of memory, still in this chapter, I make a brief overview of the principal institutions that take care of memory of the theater in Brazil. On the second chapter, I discuss on resources and procedures of acquiring and organizing an audiovisual archive, making a brief historical overview on the development and the manipulation of the technological image. In the third part, through field surveys and the bibliography used, I discuss on creation procedures, maintenance, and availability of the CPMT audiovisual archive, aiming at, not only contributing to the appreciation of theater memory, but also in providing, to artists and parties concerned, technical information on audiovisual archives in the field of theater.